Empowering Accounting Students With ‘Anak Takur Finger Code Model’: A Novel Approach to Journal Entry Skill - Adhelia Desi Prawestri (Journal of Economics and Business UBS, 2025)
This study investigates the impact of the "Anak Takur Finger Code Model" on enhancing students' comprehension of journal transaction recording, particularly among those from non-accounting educational backgrounds, as a vital preliminary step in financial statement preparation. Utilizing a Research and Development (R&D) approach guided by the ADDIE model, the research assesses the model's effectiveness in improving the understanding of first-semester accounting students across three distinct institutions. Results indicate that the "Anak Takur Finger Code Model" significantly enhances students' grasp of journal entries, demonstrated by notable improvements in pre-test and post-test scores and students' ability to articulate the method accurately. This success is attributed to its systematic approach and the integration of visual aids that facilitate the accounting learning process. It is recommended that the "Anak Takur Finger Code Model" be implemented across diverse educational settings to evaluate its effectiveness further.